A PHYLOGENETIC PLACEMENT OF DICKSONIOID FERN CALOCHLAENA JAVANICA (DICKSONIACEAE) - Bayu Adjie; Wenni Setyo Lestari (PTTI, 2014)
The genus Calochlaena was separated from Culcita in 1988, and consisting of about five species. Based on cpDNA sequences of rbcL gene, the phylogenetic tree was made and C. javanica is nested within the genus and the rest of dicksonioid ferns. The description, distribution and spore morphology are presented.